2009
DOI: 10.2174/138161209787315693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiazolidinediones Beyond Glycaemic Control

Abstract: The incidence of type 2 diabetes continues to increase in the western world over the past decade. Consequently, complications of this disease have reached crisis proportions. In addition to the classical oral hypoglycaemic agents, i.e. sulfonylureas, newer classes have emerged that work by different mechanisms such as insulin sensitizers. One such class are the thiazolidinediones (rosiglitazone and pioglitazone). These agents act as ligands for the gamma peroxisome proliferator-activated receptors (PPARs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 77 publications
(148 reference statements)
2
41
1
2
Order By: Relevance
“…The main concern with the use of PPARγ agonists, especially rosiglitazone, in the treatment of T2DM patients is the risk for adverse effects on cardiovascular safety, including the risks of heart failure, myocardial infarction, and stroke (24). Fluid retention may play an important role in the side effects of TZDs on cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern with the use of PPARγ agonists, especially rosiglitazone, in the treatment of T2DM patients is the risk for adverse effects on cardiovascular safety, including the risks of heart failure, myocardial infarction, and stroke (24). Fluid retention may play an important role in the side effects of TZDs on cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is evidence that TZDs exert a number of pleiotropic effects that may play an important role in the treatment of type 2 diabetes and potentially also in other cardiovascular disorders (12,21). These effects include favorable outcome on blood pressure and potentially anti-inflammatory net effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of PPARg agonists on inflammation is still unclear, and few studies are available regarding the potential anti-inflammatory effects of PPARg agonists in MetSyn prior to the development of diabetes. On the other hand, recent studies have suggested that PPARg agonists have other effects that may exacerbate CAD (12).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs act by stimulation of peroxisome proliferator-activated receptor-γ (PPAR-γ), which increases hepatic and peripheral insulin sensitivity by stimulating conversion of pre-adipocytes to adipocytes [24]. Adipocytes increase adiponectin, increasing insulin sensitivity.…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…Accumulating evidence also indicates that TZDs are associated with β-cell preservation [25], and some studies supports that they provide several other beneficial metabolic and vascular effects, e.g. improvement in lipid profile and blood pressure, peripheral redistribution of body fat and anti-inflammatory [24]. Their side effects, such as fluid retention and increased incidence of bone fractures, might indicate an unacceptable risk-to-benefit ratio in T2DM prevention.…”
Section: Thiazolidinedionesmentioning
confidence: 99%